Pengaruh Citra Destinasi, Kualitas Pelayanan, dan Promosi Terhadap Keputusan Berkunjung ke Objek Wisata Ecopark Ancol - Heurnius Timotius; Bonifasius MH Nainggolan (LPPM Universitas Asa Indonesia, 2023)
The purpose of this study is to determine the influence of the destination image, service quality, and promotion on visiting decisions. The sampling technique used in this research is an accidental sampling technique with quantitative methods. The population in this study were tourists who visited Ecopark Ancol. Sample data was obtained through a questionnaire that had been tested for validity and reliability which was then distributed to Ecopark Ancol visitors. The final data sample used in this research was 100 respondents. This research uses a multiple linear regression analysis method which is processed with the help of SPSS version 29 software. Based on the analysis of multiple linear regression models, it was discovered that the variables of destination image (X1), service quality (X2) and promotion (X3) had a positive and significant impact on the visit decision (Y) at Ecopark Ancol, both partially and simultaneously